Nov preizkus posebne teorije relativnosti - Strnad, Janez (Obzornik za matematiko in fiziko, 2012)
New tests of special relativity are noteworthy for some new method of measurement and not for results agreeing with the predictions of theory. A very accurate measurements of time has made possible tests at speed of some tens of meters per second and the height difference of 1/3 meter.
Keywords: fizika; merjenje časa; posebna teorija relativnosti